Eluding the illusion? Schizophrenia, dopamine and the McGurk effect - White, Thomas P.; Wigton, Rebekah L.; Joyce, Dan W.; Bobin, Tracy; Ferragamo, Christian; Wasim, Nisha; Lisk, Stephen; Shergill, Sukhwinder S. (Frontiers in Human Neuroscience, 2014)
Perceptions are inherently probabilistic; and can be potentially manipulated to induce illusory experience by the presentation of ambiguous or improbable evidence under selective (spatio-temporal) constraints. Accordingly, perception of the McGurk effect, by which individuals misperceive specific incongruent auditory and visual vocal cues, rests upon effective probabilistic inference. Here, we report findings from a behavioural investigation of illusory perception and related metacognitive evaluation during audiovisual integration, conducted in individuals with schizophrenia (n=30) and control subjects (n=24) matched in terms of age, sex, handedness and parental occupation. Controls additionally performed the task after an oral dose of amisulpride (400 mg). Individuals with schizophrenia were observed to exhibit illusory perception less frequently than controls, despite non-significant differences in perceptual performance during control conditions. Furthermore, older individuals with schizophrenia exhibited reduced rates of illusory perception. Subsequent analysis revealed a robust inverse relationship between illness chronicity and the illusory perception rate in this group. Controls demonstrated non-significant modulation of perception by amisulpride; amisulpride was, however, found to elicit increases in subjective confidence in perceptual performance. Overall, these findings are consistent with the idea that impairments in probabilistic inference are exhibited in schizophrenia and exacerbated by illness chronicity. The latter suggests that associated processes are a potentially worthwhile target for therapeutic intervention.